Kinetic and thermodynamic effects of manganese as a densification aid in yttria-stabilized zirconia. Issue 4 (April 2018) - Li, Hui; Souza, Flavio L.; Castro, Ricardo H.R.
Abstract: This work demonstrates the role of Mn as an effective sintering aid in Yttria-Stabilized-Zirconia (YSZ) is a result of the concomitant reduction of activation energies and change of interfacial energies caused by Mn segregation. Kissinger analyses of the heat of sintering showed a decrease in activation energy from 219.9 kJ/mol for YSZ to 103.4 kJ/mol for YSZ containing 3-mol% Mn. Direct microcalorimetry analyses showed that the average surface and grain boundary energies of YSZ decreased from 0.94 and 0.71 J/m 2, respectively, to 0.70 and 0.17 J/m 2 for 3-mol% Mn doped YSZ. The decrease in the ratio between surface and grain boundary energies indicates an increase in dihedral angle from 137.5° to 166.6°, meaning an increase in sintering stress. Segregation of manganese to grain boundaries was experimentally observed and is discussed to be responsible for both kinetic and thermodynamic changes in the system while suggesting interconnection by the thermodynamic extremal principle.